Geoecological foundations strengthening the stability of the national system of protected areas of the republic of Uzbekistan - Akhmadaliev Yusupjon; Abduganiev Olimjon; Makhkamov Elyorbek; Kosimov Dilshodbek; Komilova Nargiza (E3S Web of Conferences)
This study analyzes the current state, spatial structure, and development prospects of the system of protected natural areas (PNAs) in the Republic of Uzbekistan, based on the objectives set by the Kunming-Montreal Global Biodiversity Framework (GBF). Structure, coverage and integrity of the existing network of PNAs in Uzbekistan determined significant disparities among them. The analysis of them confirmed that in the regions of Uzbekistan, the coverage of PNAs by the main IUCN categories (I, II, III, IV and V) is 1.5% in Namangan region, 0.2% in Fergana region, and 0% in Andijan region were analyzed. The formation of a system of protected natural areas in these regions is guided by scientific principles aimed at preserving biological and landscape diversity, improving the ecological situation, and ensuring the rational use of natural resources. To enhance the functionality, completeness, and integrity of the protected natural areas system in the Fergana Valley, proposals were developed for establishing PNAs types.